Flavonóides, norisoprenóides e outros terpenos das folhas de Tapirira guianensis - Correia, Suzimone de J. (2008)
From hexane fraction of methanol extract of leaves of Tapirira guianensis (Anacardiaceae) were obtained lupeol, 24-methylenecycloartan-3-ol, phytol, α-amyrin, β-amyrin, sitosterol, sitostenone, glycosyl sitosterol, as well as sitosterol esterified with palmitic and stearic acids. Phytol, α-amyrin and β-amyrin esterified with fatty acids were also identified from same extract. The EtOAc extract besides the norisoprenoids (6S,7E,9S)-6,9-dihydroxy-megastigma-4,7-dien -3-one 9-O-β-glucopyranoside and (6S,7E,9R)-6,9-dihydroxy-megastigma-4,7-dien-3-one 9-O-β-glucopyranoside also afforded kaempferol 3-O-rhamnoside, kaempferol 3-O-arabinofuranoside, quercetin 3-O-rhamnoside, and kaempferol. The structural elucidation of isolated compounds were based on UV, IR, MS, ¹H and 13C NMR data analysis.